2009
DOI: 10.2478/s11756-009-0198-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of maize ZmDBP3 enhances tolerance to drought and cold stress in transgenic Arabidopsis plants

Abstract: C-repeat/dehydration-responsive element binding factors (CBF/DREBs), belonging to the AP2/ERF superfamily, play a vital regulatory role in abiotic stress responses in plants. The ZmDBP3 gene, a member of the A-1 subgroup of the CBF/DREB subfamily, was isolated from maize seedlings. The predicted ZmDBP3 protein contained a putative nuclear localization signal and an activation region. As a trans-acting factor, the ZmDBP3 protein accumulated in the nucleus in a subcellular localization assay, and activated CRT/D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…For example, OsEREBP1 and OsEREBP2 modulate the expression of OsRMC, a negative regulator of rice salt stress [21]. Overexpression of maize ZmDBP3 enhances tolerance of transgenic Arabidopsis to drought and cold stress [22]. In contrast, overexpression of the WIN 1 gene from sorghum confers drought resistance to Arabidopsis by regulating the biosynthesis of the epidermis [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, OsEREBP1 and OsEREBP2 modulate the expression of OsRMC, a negative regulator of rice salt stress [21]. Overexpression of maize ZmDBP3 enhances tolerance of transgenic Arabidopsis to drought and cold stress [22]. In contrast, overexpression of the WIN 1 gene from sorghum confers drought resistance to Arabidopsis by regulating the biosynthesis of the epidermis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Intensive research in recent years has shown that temporal and spatial modulation of stress-related TFs provides an efficient way for plants to deal with unfavourable growth conditions. TFs involved in drought response were identified and characterized in various cereal species, including all major food crops such as in rice [1][2][3][4], wheat [5][6][7][8], barley [9,10], and maize [11,12]. Overexpression of several target genes encoding stress-responsive TFs led to improved survival rate under water limitation in transgenic plants [4,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of HvDREB1 (Hordeum vulgare) activated a downstream gene rd29A and increased salt tolerance in Arabidopsis plants (Xu et al, 2009). Overexpression of ZmDBP3 (dehydration-responsive element binding protein) improved drought and cold stress tolerance in transgenic Arabidopsis plants (Wang and Dong, 2009). Overexpression of CkDBF (Caragana korshinskii dehydration-responsive element binding factor) in transgenic tobacco plants resulted in higher tolerance to high salinity and osmotic stresses and induction of a downstream target gene (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%